Serum Adropin as a Potential Biomarker for Predicting the Development of Type 2 Diabetes Mellitus in Individuals With Metabolic Dysfunction-Associated Fatty Liver Disease - Li, Na; Xie, Guomin; Zhou, Biao; Qu, Aijuan; Meng, Hua; Liu, Jia; Wang, Guang (Frontiers in Physiology, 2021)
Background: Adropin, a peptide translated from the Energy Homeostasis Associated gene (ENHO), was mainly expressed in the liver and was a regulator in metabolic and energy homeostasis. This study aims to investigate the correlation between adropin and histological characteristics of the liver, and the clinical relevance of adropin in patients with metabolic dysfunction-associated fatty liver disease (MAFLD). Methods: A total of 62 subjects, including 32 healthy controls and 30 MAFLD patients, were enrolled in this case-control study. The MAFLD patients were further divided into two subgroups, including NGT-M group and T2DM-M group. Serum adropin levels, metabolic parameters and intrahepatic lipids, the liver ENHO mRNA expressions and histological characteristics were investigated. Results: MAFLD patients showed significantly lower circulating adropin compared with healthy controls (2.02 ± 2.92 vs. 5.52 ± 0.65 ng/mL, P < 0.0001). Subgroup analysis exhibited dramatically declined serum adropin levels in T2DM-M patients compared with NGT-M group (0.51 ± 0.73 vs. 4.00 ± 3.52 ng/mL, P < 0.001). H&E and Oil Red O staining show exacerbated steatohepatitis in T2DM-M patients in contrast with NGT-M group. Furthermore, serum adropin concentrations were negatively correlated with intrahepatic triglyceride (TG), total cholesterol (TC) and NAFLD activity score (NAS) (TG: r = -0.495; TC: r = -0.392; NAS: r = -0.451; all P < 0.05). Conclusions: MAFLD patients showed significantly lower adropin levels than the healthy controls, especially in T2DM patients. Adropin maybe a potential biomarker for predicting the development of MAFLD, especially in T2DM individuals.